Development of a drug delivery agent based on ionic liquids templated mesoporous silica nanoparticles - Mohamed Isa, Eleen Dayana (2017)
Mesoporous silica nanoparticles (MSNs) has been used as drug delivery agents since 2001 and this is due to their properties such as easy manipulation of physical characteristic, inert, great biocompatibility and easy functionalization. Up to the current date, the most establish template to generate MSNs is anionic surfactant such as cetyltrimethylammonium bromide (CTAB). With the discovery of ionic liquids (ILs), the template materials for MSNs no longer limited to CTAB. This is due to the similarity of core structure between CTAB and ILs which consist of large organic cations and inorganic or organic anions. The most interesting parts regarding ILs is different combination of cations and anions will change the ILs’ properties. Therefore, by changing the anions or cations, there is a possibility of obtaining MSNs with different morphologies. In this work, a series of long chain pyridinium ILs (CnPyBr where n = 12, 14, 16 and 18), two long chain imidazolium ILs (CnMIMBr where n = 16 and 18) and four pyridinium ILs with different anions (C16PyX where X = BF4, NO3, ClO4 and CF3COO) were used as templates to synthesized MSNs. By using these different types of ILs, several studies were conducted such as the effect of alkyl chain length, synthesis method, cation and anions. To study the effect of synthesis method, two methods were employed and both syntheses utilized triethanolamine (TEA) as the base catalyst where in one method the TEA undergo pre-treatment process while the other did not. The pre-treatment process involved the heating of TEA and silica source together prior its addition to template water mixture. Besides that, the effects of pyridinium ILs alkyl chain length were also investigated. MSNs generated via both methods exhibited spherical morphology and decreasing average particles size with increasing alkyl chain length of pyridinium ILs. The MSNs porosity were further analyzed through nitrogen sorption analysis where the surface area were in between 71.85 m2 g-1 to 525.02 m2 g-1 and the pore volume was up to 1 cm3 g-1. It was found that between the two syntheses, the one without pre-treatment process generated MSNs with larger surface area value. Thus, the method without the pre-treatment was chosen to study the effect of cation and anions. Two imidazolium ILs were used to study the effect of cation and it was found that the MSNs produced using these templates exhibited slightly smaller particles size (50.24 and 34.52 nm) and higher surface area value (570.61 and 598.71 m2 g-1) compared to its counterpart of pyridnium ILs. Anions effect study indicated that different anions exhibited different particles morphology. Some of the morphologies exhibited were spherical, distorted spherical, raspberry and undefined shape with surface area ranging from 92.65 m2 g-1 to 494.96 m2 g-1. From all these previous study, C16PyBr was chosen as the template to be optimized using Response Surface Methodology (RSM) and Box-Behnken Design (BBD) was used. In this design, there were three factors manipulated which were mass of IL, mass of TEA and temperature and two responses were surface area and particles size. From the statistical analysis, surface area and particle size responses were fitted into linear and quadratic models respectively. One MSNs was then chosen from the statistical data for the application in drug delivery studies and the chosen MSNs has the surface area of 999.051 m2 g-1 and average particles size of 28.5 nm. In drug loading studies, evaporation method was chosen and a total of 37 % of drug was successfully encapsulated. Drug release study was conducted in 48 hours and about 32 % of drug has been released. Drug release kinetics study indicated that the release follows the zero order and Hixson-Crowell model.